2021
DOI: 10.1186/s12909-021-02590-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectivity of near-peer teaching in training of basic surgical skills – a randomized controlled trial

Abstract: Background Near-peer teaching (NPT) is a special way of teaching where the tutor is one or more academic years ahead of the person being tutored. The literature agrees on the benefits of the method, but there are only a few publications examining its effectiveness using objective methods. The aim of our study was to examine the effectiveness of NPT in the training of basic surgical skills. Methods We included 60 volunteer students who participated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…We assessed students' efficacy in knot tying and suturing by online method, using OSATS scores correspondent for the past years [16,31], then evaluated them in comparison with results from the previous two years.…”
Section: Evaluation Of the Tasks And The Feedback Of The Studentsmentioning
confidence: 99%
“…We assessed students' efficacy in knot tying and suturing by online method, using OSATS scores correspondent for the past years [16,31], then evaluated them in comparison with results from the previous two years.…”
Section: Evaluation Of the Tasks And The Feedback Of The Studentsmentioning
confidence: 99%
“…Near-peer teaching (NPT) represents an alternative teaching approach that relieves the burden of traditional faculty-led teaching [ 13 ]. In this approach, the instructor is a person who is one or more years senior to another while being on the same level of educational training — for instance, senior medical students and junior medical students [ 4 , 5 , 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are distinct theoretical features of NPT that underlie the effectiveness of this approach. These include, but are not limited to, reduced educational distance between the teacher and learner, a less formal educational setting, and smaller learner group sizes [ 13 , 24 , 25 ]. Moreover, NPT is advantageous to the peer instructors themselves, as it provides an opportunity for students to develop teaching skills in a low-pressure environment while enhancing their own knowledge [ 15 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Covid-19 TAs alsodeveloped as medical educators, as part of the medical school's Clinical Educator Programme (CEP), which ran a series of workshops and online modules on medical education for the tutors.A group of new graduates also developed an online Ophthalmology revision programme for students, in partnership with ophthalmologists based in Edinburgh, which was well received and demonstrated the impact of near-peer teaching. It is interesting to note that a recent study into the effectivity of near-peer teaching found it to be mutually benefit and to have a positive impact on student development [2].…”
mentioning
confidence: 99%